PENINGKATAN KOMPETENSI GURU PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI (STUDI PADA PPMG DINAS PENDIDIKAN ACEH) - Hasan Basri (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
The existence of the Teacher Quality Development Center (PPMG) is still questioned when the quality of education is declining where the issue of the quality of education in Aceh is low. Some education observers immediately highlighted PPMG as the party most responsible for the low quality of education. The low quality of teachers in Aceh suspected that PPMG has not carried out its functions properly. This study focuses its study on the role and function of PPMG in improving the competence of Islamic religious education teachers and character by using data collection techniques: observation, documentation, and interviews. While the sample is taken by purposive sampling technique, which is the determination of the sample aimed at certain considerations. In this context, the sample was PPMG Wilayah VII Meulaboh in coordination with the Education Offices of West Aceh, Nagan Raya, and Aceh Jaya Districts. The data analysis technique used in this research is qualitative-descriptive analysis. The results of the study prove that: 1) PPMG Aceh Education Agency, in this case, PPMG Wilayah VII Meulaboh, has played its role and carried out its functions procedurally but has not been optimal in efforts to improve the quality of Islamic religious education teachers and manners; 2) The implementation of the competency development program for Islamic religious education teachers and manners has been carried out effectively and efficiently; 3) The quality improvement system of Islamic religious education teachers and character conducted by PPMG in Aceh Province uses a scientific approach that refers to the implementation of the 2013 National Curriculum (K-13). The system for enhancing teacher pedagogical competence is pursued by providing training in classroom management, learning design, and civilizing literacy.